Packaging Design of Milkfish Products in Tambak Oso Village Sidoarjo - Dyan Agustin; Widyasari; Sonja Andarini (Nusantara Science and Technology Proceedings)
Increased marketing of a product can be done through the improvement of packaging design. Good packaging design is a design that is able to provide better information, more secure, more complete and interesting in marketing a product, especially processed products produced by community communities Tambak Oso Sidoarjo Village.The purpose of this research is to produce new packaging design, interesting and safe from processed product of milkfish that have been produced. Analysis technique used from this research is to use SWOT analysis to know the advantages, weaknesses, opportunities and threats of processed milkfish products that already exist. The analysis results obtained that in terms of form produced 3 (three) forms with different functions. Single rectangular base pack pattern, secondary packaging form there are additional tongue, tertiary packaging form there are two kinds, the first form of bag that can accommodate a maximum of 3 pieces of single pack and the second box-shaped containing 5 to 10 single pack. The material used from laminate art carton material on the outside and glossy laminate on the inside. For color use combination of brown, gray, yellow and black. As for the logo and the name still use the old because it was recorded at the time of permitting process.